REDUKSI KADAR LEMAK DAN KOLESTEROL TELUR PUYUH YANG DIBERI PAKAN SERBUK DAUN SELIGI (Phyllanthus buxifolius Muell) SEBAGAI FEED SUPPLEMENT - Y. Ta'inidari; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2013)
The aim of this study to sought determine effect of seligi leaf powder (Phyllanthus buxifolius, Muell) as a feed supplement on body weight, feed consumption, fat and cholesterol level of egg quails. Eighteen of quails have aclimated for 14 days, randomly divided into 3 group and each group have treated 0, 2,5 and 5% powder of seligi leaf in feed for 7 days. The result of this study shown powder of seligi leaf significant (P< 0,05) influence on body weight, feed consumption, and fat and cholesterol level of egg quails, but not significant (P>0,05) influence on internal quality off egg. Average of body weight quail in tread without powder of seligi leaf significant (P<0,05) lower than 2,5% and 5% powder of seligi leaf in feed, the average consumption of the quail treated with 2.5% and 5% significant (P <0.05) lower than the diet without leaf powder seligi, the average fat content of the treated 2.5% and 5% lower than the diet without seligi leaf powder, the average cholesterol levels treated with 2.5% and 5% lower than the diet without seligi leaf powder. It’s can be concluded that the use of seligi leaf powder in the ration of 2.5%-5% can reduce levels of fat and cholesterol 1,01-1,65% and 0,99-1,38%, respectively without influence on internal quality of quail eggs. Keywords: seligi, quail, feed intake, fat and cholesterol